The Effect of Surface Coating of Iron Oxide Nanoparticles on Magnetic Resonance Imaging Relaxivity - Ahmadpoor, Fatemeh; Masood, Atif; Feliu, Neus; Parak, Wolfgang J.; Shojaosadati, Seyed Abbas (Frontiers in Nanotechnology, 2021)
Iron oxide nanoparticles (IONPs) with acceptable biocompatibility and size dependent magnetic properties can be used as efficient contrast agents in magnetic resonance imaging (MRI). Herein, we have investigated the impact of particle size and surface coating on the proton relaxivity of IONPs, as well as engineering of small IONPs' surface coating as a strategy for achieving gadolinium free contrast agents. Accordingly, polymer coating using poly(isobutylene-alt-maleic anhydride) (PMA) with overcoating of the original ligands was applied for providing colloidal stability to originally oleic acid capped IONPs in aqueous solution. In case of replacement of the original ligand shell the polymer had been modified with dopamine. Furthermore, the colloidal stability of the polymer coated IONPs was evaluated in NaCl and bovine serum albumin (BSA) solutions. The results indicate that the polymer coated IONPs which involved replacement of the original ligands exhibited considerably better colloidal stability and higher proton relaxivity in comparison to polymer coated IONPs with maintained ligand shell.